The Effect of TGT (Team game tournament) type Cooperative Learning Model Assisted by Interactive Wordwall Media on the Interests and Science Learning Outcomes of Junior High School Students - Luh Putu Yeni Andriyani; I Nyoman Tika; Putu Artawan (Jurnal Penelitian Pendidikan IPA, 2025)
To improve students' interest and learning outcomes in science, it is necessary to apply an innovative learning model assisted by interactive media so that the learning process in the classroom becomes more interesting, so that it can increase students' interest in learning which will later affect student learning outcomes. One innovation that can be applied to improve students' interest and learning outcomes is to use an innovative learning model, namely the TGT (Team Game Tournament) cooperative learning model assisted by interactive wordwall media. This study aims to describe the differences in students' interest in learning science, students' learning outcomes, interests and learning outcomes of science simultaneously in students who are taught using the TGT type cooperative learning model assisted by interactive wordwall media with students who are taught using the TGT type cooperative learning model. This type of research is a quasi-experimental researchs. This study uses a quantitative approach. The design of this study uses the Nonequivalent Pretest Posttest Control Group Design. The results of this study indicate that: a significance value of less than 0.05 was obtained, a significance value of less than 0.05 was obtained, a value of less than 0.05 was obtained, so it can be concluded that there are differences in interest and learning outcomes simultaneously in groups of students who are taught using the TGT type cooperative learning model assisted by interactive wordwall media with students who are taught using the TGT type cooperative learning model.